A Novel D-Psicose 3-Epimerase from Halophilic, Anaerobic IIocasia fonsfrigidae/I and Its Application in Coconut Water - Wulansari, Shinta; Heng, Sobroney; Ketbot, Prattana; Baramee, Sirilak; Waeonukul, Rattiya; Pason, Patthra; Ratanakhanokchai, Khanok; Uke, Ayaka; Kosugi, Akihiko; Tachaapaikoon, Chakrit (International journal of molecular sciences, 2023)
D-Psicose is a rare, low-calorie sugar that is found in limited quantities in national products. Recently, D-psicose has gained considerable attention due to its potential applications in the food, nutraceutical, and pharmaceutical industries. In this study, a novel D-psicose 3-epimerase (a group of ketose 3-epimerase) from an extremely halophilic, anaerobic bacterium, Iocasia fonsfrigidae strain SP3-1 (IfDPEase), was cloned, expressed in Escherichia coli, and characterized. Unlike other ketose 3-epimerase members, IfDPEase shows reversible epimerization only for D-fructose and D-psicose at the C-3 position but not for D-tagatose, most likely because the Gly218 and Cys6 at the substrate-binding subsites of IfDPEase, which are involved in interactions at the O-1 and O-6 positions of D-fructose, respectively, differ from those of other 3-epimerases. Under optimum conditions (5 µM IfDPEase, 1 mM Mn[sup.2+], 50 °C, and pH 7.5), 36.1% of D-psicose was obtained from 10 mg/mL D-fructose. The IfDPEase is highly active against D-fructose under NaCl concentrations of up to 500 mM, possibly due to the excessive negative charges of acidic amino acid residues (aspartic and glutamic acids), which are localized on the surface of the halophilic enzyme. These negative charges may protect the enzyme from Na[sup.+] ions from the environment and result in the lowest pI value compared to those of other 3-epimerase members. Moreover, without adjusting any ingredients, IfDPEase could improve coconut water quality by converting D-fructose into D-psicose with a yield of 26.8%. Therefore, IfDPEase is an attractive alternative to enhancing the quality of fructose-containing foods.